One of the Great Pioneers of Anatomy: Gabriele Falloppio (1523-1562) - Çağatay ÖNCEL (Bezmiâlem Science, 2016)

(untitled)
Gabriele Falloppio (1523–1562) was one of the greatest anatomists of medical history. He discovered and named numerous parts of the human body. This review aims to report some information regarding his life and studies.